Molecular characterization of 18S rDNA partial sequence in Microcosmus (Stolidobranchiata, Pyuridae) - FULGIONE, D.; RIPPA, D.; DE LUCA, A.; MILONE, M. (Mediterranean Marine Science, 2006)
We present a 18S rDNA based molecular phylogeny of two species of the genus Microcosmus (M. sulcatus and M. claudicans) sampled in the Mediterranean, to investigate their phylogenetic position relative to species of the order Stolidobranchiata. The analysis is based on partial sequences (739 bp) of the 18S rDNA. Among the 18 variable sites found between the two species, 4 correspond to transitions (ts), 14 to transversions (tv) and 4 to deletions/insertions. In the considered Stolidobranchiata, we found 4.3% overall mean number of nucleotide differences and 0.06 (S.E. ±0.01) Kimura 2-parameter distance. The mean number of nucleotide differences between Microcosmus spp. and other Stolidobranchiata species was of 6% and 0.08 (S.E. ±0.01) Kimura 2-parameter distance. A molecular phylogeny obtained by Maximum Parsimony corroborates results of the traditional taxonomy.